2014
DOI: 10.5455/ajvs.167205
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Iidentification of Klebsiella Microbe Isolated from Chicks

Abstract: Klebsiella pneumoniae is one of the most common infectious disease affecting chicks, causing great economic losses. Also, possess food safety and antimicrobial resistance threats, as it may act as a contamination source of poultry meat and eggs. We aim to isolation and identification of klebsiella organisms causing death and loss in chicks. To perform this aim, it is necessary to full following points: Isolation of klebsiella causing respiratory manifestations and death in chicks purification and identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In general, the investigation of 160 samples collected from clinically diseased broiler chickens revealed that the prevalence rate of K. peumoniae was (14.4%) as shown in (Table 2). Nearly similar results were recorded by Aly et al (2014) and Khalda et al (2000) who recorded that the prevalence rate of K. peumoniae in broiler chickens was (10%) and (10.2%), respectively.On the other hand, Turkyilmaz ( 2005) recorded a higher prevalence rate (47.1%). Meanwhile, Dashe et al (2013) and Abdulrazzaq et al (2014) reported that the prevalence of K. peumoniae in broiler chickens was (8%) and (7%), respectively.…”
Section: Discussionsupporting
confidence: 86%
“…In general, the investigation of 160 samples collected from clinically diseased broiler chickens revealed that the prevalence rate of K. peumoniae was (14.4%) as shown in (Table 2). Nearly similar results were recorded by Aly et al (2014) and Khalda et al (2000) who recorded that the prevalence rate of K. peumoniae in broiler chickens was (10%) and (10.2%), respectively.On the other hand, Turkyilmaz ( 2005) recorded a higher prevalence rate (47.1%). Meanwhile, Dashe et al (2013) and Abdulrazzaq et al (2014) reported that the prevalence of K. peumoniae in broiler chickens was (8%) and (7%), respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Klebsiella species are observed in human and animal stools, containers of water, and personal water (slama et al, 2010). Klebsiella pneumoniae is a prevalent infectious illness that affects chicks and causes significant economic losses (Aly et al, 2014). The respiratory illness is characterized by dyspnea, pump handled respiration, gasping, mucous discharge, facial edema, sinus enlargement, tracheitis, exudative pneumonia, pleuritis, air saculitis, pericarditis, reduced egg production, and low egg quality (Tantawy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, they are opportunistic bacteria that may potentially infect the urinary system or lungs in humans [12,13]. Klebsiella pneumoniae is one of the pathogens of the respiratory system responsible for high mortality in broiler chicks and hens [14,15]. Numerous studies have confirmed the possibility of the transmission of ESBL-producing Klebsiella spp.…”
Section: Introduction and Objectivementioning
confidence: 99%